THE BECOMING OF THE LITERATURE? CHARACTERIZATION IN THEODOSIUS HAGIOGRAPHY OF SAINT SAVA – POSSIBLE INFLUENCE FROM HAGIOGRAPHY OF BARLAAM AND JOSAPHAT (Philological Studies, 2019)
The paper considers the characters from the Hagiography of Barlaam and Josaphat as possible models for the formation of the heroes of Theodosius Hagiography of Saint Sava. The characterization of Saint Simeon is at the center of the interpretation, and the ways in which it is performed in medieval Serbian literature is considered. The characters of Saint Simeon and Emperor Avenir are compared and similarities are considered. The significance of the function of the conflict between father and son in the structure of interpreted works is emphasized. The characters of the sons, the prince Josaphat and Saint Sava are compared, and the interpretation highlights the scene of his encounter with the Russian monk. The question of the relation between faction and fiction, history and literature is theoretically problematized. There are examples of the negative imaging of the means of government, on which the foundation of the analyzed characterization model is based. The aim of the study is to initiate a reflection of the way the foundations of Serbian literature are derived through the use of already existing models in the Byzantine tradition.
Keywords: Hagiography of Barlaam and Josaphat, Theodosius, Saint Simeon, Saint Sava, hagiography, model of characterization, history, historiographic metafiction